2016
DOI: 10.1007/s11912-016-0500-6
|View full text |Cite
|
Sign up to set email alerts
|

Health Services Research and Regionalization of Care—From Policy to Practice: the Ontario Experience in Head and Neck Cancer

Abstract: Patients being treated at higher case volume hospitals or by higher case volume physicians appear to have better outcomes. This volume-outcome relationship is reviewed for oncologic and non-oncologic surgery with a focus on head and neck oncology. The impact of these research findings on health policy and health-care organization in Ontario, Canada, is then outlined. Lastly, future directions for quality improvement in surgical oncology are reviewed in the context of a universal health-care system. These inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
(33 reference statements)
3
23
0
2
Order By: Relevance
“…[9][10][11] Regionalization of hospital care has been advocated based on a significant volume-outcome association, but arguments against regionalization cite unintended consequences of limiting access for populations dependent on smaller hospitals for care, and an adverse impact on the financial health of these hospitals and communities. 11,27,28 Our data support moving beyond structural measures such as volume alone as the main criterion for identifying high-performing centers. Ultimately, the inclusion of process measures emphasizes quality over quantity alone and will encourage all hospitals and physicians to provide NCCN guideline-compliant care.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…[9][10][11] Regionalization of hospital care has been advocated based on a significant volume-outcome association, but arguments against regionalization cite unintended consequences of limiting access for populations dependent on smaller hospitals for care, and an adverse impact on the financial health of these hospitals and communities. 11,27,28 Our data support moving beyond structural measures such as volume alone as the main criterion for identifying high-performing centers. Ultimately, the inclusion of process measures emphasizes quality over quantity alone and will encourage all hospitals and physicians to provide NCCN guideline-compliant care.…”
Section: Discussionsupporting
confidence: 61%
“…This is an important observation, as hospital volume has been shown to be associated with improved outcomes for larynx cancer care, but the use of hospital volume as a proxy for quality is controversial . Regionalization of hospital care has been advocated based on a significant volume–outcome association, but arguments against regionalization cite unintended consequences of limiting access for populations dependent on smaller hospitals for care, and an adverse impact on the financial health of these hospitals and communities . Our data support moving beyond structural measures such as volume alone as the main criterion for identifying high‐performing centers.…”
Section: Discussionsupporting
confidence: 51%
“…If difficult cases require more complex surgery or specialized radiation and are considered outside the expertise of CCP and CCCP, they may require referral to AC. The model of regional head and neck centers relies on the concept that surgeons who experience a greater volume of cases are more likely to have an armamentarium of specialized surgical techniques and follow standard‐of‐care treatment algorithms, which should result in better outcomes …”
Section: Discussionmentioning
confidence: 99%
“…Without question, the volume of surgical cases performed by a surgeon correlates with better results. Numerous studies have shown that high‐volume surgeons have lower complication rates, shorter operative times, and better outcomes . Proving that for parotidectomy, however, has not been done and most likely will not be done.…”
mentioning
confidence: 99%
“…Numerous studies have shown that high-volume surgeons have lower complication rates, shorter operative times, and better outcomes. [1][2][3][4] Proving that for parotidectomy, however, has not been done and most likely will not be done.…”
mentioning
confidence: 99%